PENGARUH INDEPENDENSI AUDITOR, DUE PROFESSIONAL CARE, FEE AUDIT DAN PERIKATAN AUDIT TERHADAP KUALITAS AUDIT - Ana Rizkiatus Sa’adah; Auliffi Ermian Challen (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2022)
This study aims to examine whether there is an influence of auditor independence, due professional care, audit fees and audit tenure on audit quality. The population in this study were auditors who worked at KAP in East Jakarta. The number of samples in this study were 67 respondents. The sampling technique uses purposive sampling method. The research method used is quantitative with primary data sources. The methode of data analysis uses multiple linear regression analysis with SPSS version 25. The results of this study provide empirical evidence that partially auditor independence variables, due professional care, audit fees and audit tenure in a positive direction have a significant effect on audit quality. Simultaneously the auditor independence variables, due professional care, audit fees and audit tenure with a positive direction have a significant effect on audit quality.